1990
DOI: 10.1111/j.1439-0310.1990.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity Breeds Tolerance: the Development of Social Stability in Flocking Siskins (Carduelis spinus)

Abstract: Behavioural integration associated with the fusion of two flocks is analyzed in captive siskins (Carduelis spinus) by quantifying changes in social behaviour with time since joining. In general there was an increase in the incidence of tolerant behaviour, supplanting attacks and hopping withdrawals with time since fusion of the flocks. However, the number of displays and flights showed the opposite, negative, trend. Taking dominance status into account, the greatest change in behaviour with time since joining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 21 publications
(9 reference statements)
2
37
0
Order By: Relevance
“…Since residency is not related to the black bib size, it is probably not either related to personality, and hence, the dominance of residents over transients is not expected to result from a behavioural syndrome but from a difference in prior residency. This is supported by the plasticity in social interactions among flock members of different groups joined together found in a previous study (Senar et al 1990a). Since resident and transient siskins differ in wing shape (Senar et al 1994), body mass regulation (Senar et al 2001) and vigilance (Pascual et al 2014), residency in Eurasian siskins is probably a polymorphic trait (i.e.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Since residency is not related to the black bib size, it is probably not either related to personality, and hence, the dominance of residents over transients is not expected to result from a behavioural syndrome but from a difference in prior residency. This is supported by the plasticity in social interactions among flock members of different groups joined together found in a previous study (Senar et al 1990a). Since resident and transient siskins differ in wing shape (Senar et al 1994), body mass regulation (Senar et al 2001) and vigilance (Pascual et al 2014), residency in Eurasian siskins is probably a polymorphic trait (i.e.…”
Section: Discussionsupporting
confidence: 54%
“…However, two other studies seem to support the dear-enemy effect. In the first study, it was found that the social relationships between a resident and an intruder group of siskins that were joined together stabilized after 20 days, with a high increase in tolerant behaviour between the members of both groups and a reduction in the dominance of prior residents over intruders (Senar et al 1990a). In the second study, it was found that transients interacted with other transients more often than expected and residents with other residents less than expected (Senar et al 1990b).…”
Section: Discussionmentioning
confidence: 97%
“…To ensure familiarity between the three birds, they were retained in their same groups for at least two months over the winter, before starting the mate-choice experiments. Previous studies have determined that familiarity in siskins is attained after 20 days of cohabiting in the same cage [48]. Our period of at least two months is therefore more than sufficient time for the three birds to become familiar.…”
Section: Methodsmentioning
confidence: 92%
“…cardueline finches, like siskins, crossbills and citril finches, breed in semicolonies that have high social interaction among their members [80,82]. The high social costs of flock switching enhance membership stability [48,[83][84][85][86], and data on siskins and other finches suggest that flocks formed in the original breeding localities probably remain together in the wintering grounds [86]. In this scenario, if birds develop a mating preference for familiar birds, flock structure would favour pairing with individuals from the same breeding subpopulation, thereby reducing gene flow and allowing local adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…As serins have a highly despotic social system (Senar et al 1997), we predicted that males would preferentially attack females, the subordinate fraction of the population. Conversely, as siskins display a feudal social system with like-vs-like aggression (Senar et al 1990a(Senar et al , 1997Ripoll et al 2004), we predicted that males would preferentially attack other males. We additionally predicted differences in sex ratios between the two species at the end of the winter.…”
mentioning
confidence: 99%